Seeking by a shareholder of a simple joint-stock company redress for damage caused to the company (Discourse of Law and Administration, 2024)
he purpose of this article is to discuss and systematize issues related to the possibility of a shareholder of a simple joint-stock company bringing an action for compensation for damage caused to the company (actio pro socio). The comments made constitute a voice in the discussion, and the proposed changes may contribute to increasing the effectiveness of the analyzed institution. In particular, the article draws attention to issues related to the group of entities authorized to bring a complaint, the scope of the complaint (premises), liability for filing a complaint, as well as the legitimacy to initiate enforcement proceedings in connection with obtaining a judgment granting a claim for compensation for damage. The conclusion stated, among other things, that the scope of application of the claim in question in simple joint-stock company should cover not only damage caused by a member of the body or a shareholder, but, as in the case of a limited liability company, and a joint-stock company, the claim should cover damage caused to the company by each entity. Therefore, de lege ferenda, the appropriate wording of the provisions of the Commercial Companies Code was proposed.
Keywords: actio pro socio; simple joint-stock company; shareholder complaint; damage